Evaluation of the regional programme for Europe and the CIS, 2011-2013 (United Nations Development Programme, Evaluation Office, 2013)
"This evaluation covered the Regional Programme for Europe and the Commonwealth of Independent States (CIS) 2011-2013, implemented by the UNDP Regional Bureau for Europe and the CIS, through its Regional Centre in Bratislava. It examined the results achieved by the regional programme articulated in seven outcomes under the four topical areas: response to climate change, social inclusion, local development, and promotion of new partnership in development cooperation. The evaluation report includes findings and conclusions and provides recommendations for improvement. The UNDP management response is included as an annex to the evaluation report."--Publisher website